Decision Making and Case Attrition in Rape Cases: A Feminist Jurisprudence Perspective - Lebitse, Palesa (University of the Witwatersrand, Johannesburg, 2025)
This study is an empirical study of prosecutorial attrition in rape cases. The study uses mixed methods (quantitative and qualitative) to examine data derived from Umlazi Police Station in KwaZulu Natal. This thesis is approached from a feminist jurisprudence perspective to analyse legal texts that critically identify gender inequalities. Feminist critical theorists predict that external factors in the legal system that go beyond the actual legal burden influence the outcome of cases. This study tests the hypothesis, among others, that many of the decisions to decline prosecution in cases of rape are based on extra-judicial factors such as the complainant-perpetrator relationship; the complainant’s character; and/or their credibility that contributes to or causes case attrition. In cases of rape, extra-legal variables are believed to have a significant influence on the decisions and actions of the key players within the criminal justice system. The results of this study make it possible to examine any correlation between procedural obstacles and outcomes in South Africa. With these findings, we can gain insight into the impact of rape law reform on the prosecution of cases in South Africa, taking into account the subcultural theory and downstream theory of rape.
Thesis submitted in fulfilment of the requirements of the Degree of Doctor of Philosophy, to the Faculty of Commerce, Law and Management, School of Law, University of the Witwatersrand, Johannesburg, 2024
Keywords: Rape; Attrition; Prosecutors; Decision Making; Procedure; Evidence; UCTD; SDG-5: Gender equality; SDG-16: Peace, justice and strong institutions